THE USE OF GAMIFICATION METHOD TO IMPROVE NINTH GRADE STUDENTS’ READING COMPREHENSION IN DESCRIPTIVE TEXT AT SMP NEGERI 7 PEMATANG SIANTAR - Isabel selmiola sabrina; Dwi Angeli Pardede; Gabriella Pardede; Bella Sonia Sianturi; Dumaris E Silalahi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2025)
Reading comprehension plays a crucial role in English language learning, as itenables students to understand written texts and construct meaning effectively.However, many EFL students still experience difficulties in comprehendingdescriptive texts due to low motivation and the continued use of teachercenteredinstructional practices. Although previous studies have reportedpositive outcomes of gamification in language learning, limited research hasspecifically examined its effectiveness in improving students’ readingcomprehension of descriptive texts in junior high school contexts. Therefore,this study aims to investigate the effectiveness of the Gamification Method inenhancing ninth-grade students’ reading comprehension at SMP Negeri 7Pematangsiantar. A quasi-experimental design was employed, involving anexperimental group taught using gamified activities through Quizizz andKahoot, and a control group taught using conventional methods. Each groupconsisted of 30 students, and data were collected through pre-tests and posttests.The findings revealed that both groups showed improvement after thetreatment; however, the experimental group achieved a higher post-test meanscore (85.17) than the control group (83.17). The Independent Samples t-testresult indicated a statistically significant difference between the two groups (p <0.05). In conclusion, the study confirms that the Gamification Method iseffective in improving students’ reading comprehension of descriptive texts byincreasing their motivation, engagement, and learning achievement..Keyword : Reading Comprehension, Descriptive Text, Gamification Method,EFL Students, Junior High School